BUKU GOOGLE SEBAGAI PERPUSTAKAAN DIGITAL ERA GENERASI MILENIUM DAN GENERASI ZET - Jamridafrizal Jamridafrizal; Herlina Pratiwi (Maktabatuna, 2019)
Today's Information Users prefer information that  is  available  online.  This online information is clearly easier to find, faster and cheaper and more suitable for hobbies with those who like to surf the internet. Google books as one of online resources can be hernessed to find information for academic needs, especially writing scientific papers. The Google ebook database is not yet widely known and utilized by today's information seekers. In order for this facility to be "eye catching" for today's information seekers there needs to be a deliberate effort by librarians and library managers. The purpose of this reset is how to use google books online efficiently and effectively